Young Woman with Early Stage Nasopharyngeal Carcinoma: A Rare Case - Benny Kurnia; Fadhlia; Lily Setiani; Juniar; Ridha Chaharsyah Mulya (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2021)
Introduction: Nasopharyngeal carcinoma (NPC) is the most often cancer occurs in the head and neck. Early stage NPC is difficult to diagnose clinically, most NPC patients have been diagnosed in advanced stages. The study presents a case of early-stage NPC with the symptoms of recurrent nosebleeds and headache which can be early symptom to suspect NPC. Case report: We reported a case of 27-year-old woman patient with chief complaints recurrent nosebleeds since 2 months ago frequently one to two times a week. Patients also complained of mild headaches, but getting better by taking a rest and patient also had a history of tinnitus since 2 month ago. The patient has a habit of consuming salted fish and preservative food since childhood. Based on his history of illness, physical examination, imaging, and histopathology, we concluded that he was diagnosed with Nasopharyngeal Carcinoma T1N0M0, and the patient are going to reffered to North Sumatera or central java to get radiotherapy. Conclusion: Early stage of nasopharyngeal cancer is a rare condition at Aceh, the fastest we found early stages will increased survival rate.